Assessment of Interleukin-1β in Saliva of Smoker and Non-smoker Patients with Chronic Periodontitis. - Solav Abdul-Qadir Mustafa; Haween T. Nanakaly; Hozan Wrya Azeez (Erbil Dental Journal, 2022)
Background and objectives: Smoking is considered a significant risk factor in periodontitis. The pathogenesis of periodontal disease may be affected by alterations of the inflammatory response by smoke. Interleukin-1 (IL-1β), an effective pro-inflammatory cytokine have been associated with the immunopathology of periodontitis. The aim of this study was to assess the levels of IL-1β in saliva from smokers and non-smokers with chronic periodontitis and periodontally healthy controls. Materials and methods: Gingival index, Plaque index, probing pocket depth, clinical attachment level, bleeding on probing were assessed in 84 subjects who were equally divided in to three groups. group I periodontally healthy non-smoking subjects ; group II non-smokers with chronic periodontitis; group III smokers with chronic periodontitis; Enzyme Linked Immunosorbent Assay (ELISA) test was used for quantification of Interleukin (IL)- 1β in the saliva samples. Statistical analysis were performed with SPSS version 22.0. Results: Interleukin-1β level in saliva was significantly higher in smoker than in nonsmokers with chronic periodontitis and the controls (P˂ 0.001). In subjects with chronic periodontitis, a significant correlation existed between CAL and IL-β (r= 0.313, p= 0.052) among non-smokers; there was also a highly significant positive correlation between, CAL and IL-β (r= 0.310, p= 0.051), BOP and IL-β (r= 0.333, p= 0.05) among smokers. Conclusion: Salivary IL-1β level were significantly elevated in periodontitis patients. Smokers with chronic periodontitis exhibited a highly significant increase in salivary IL-1β levels. Hence, this reflects the impact of smoking on immune response and its role in the pathogenesis of periodontal disease.